MOTIVASI PEMERINTAH INDONESIA MENERAPKAN KEBIJAKAN KERINGANAN PAJAK TERHADAP INVESTOR ASING YANG MASUK KE INDONESIA TAHUN 2015 - Angela, Anastasia Sarah; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This present research describes the motivation of Indonesia Government to implementation of tax allowance policy for foreign investor that will invest in Indonesia in 2015. Global economic crisis and increase of United States economic has impact for economic of Indonesia. In 2014 Indonesia has defisit for trade and moneter transaction.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze